2020
DOI: 10.3390/w12041121
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Nitrogen Sources in the Eocene Aquifer Area (Palestine)

Abstract: Groundwater is the main source of water in many countries all over the world. Prevention of the pollution of this source is essential for a sustainable utilization. Nitrate pollution of groundwater is a common problem due to the association between intensive agriculture to achieve food security and fertilization. For an efficient management of groundwater pollution from nitrate, the first step would be to quantify the different sources of nitrogen in the aquifer of concern. This paper aims at demonstrating a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Various research works confirmed and discussed this negative outcome [48]. On-ground contaminants are easily infiltrated and leached to the shallow wells, whereas deep wells are more protected [2]. Infiltrated contaminated water follows mixing processes through its way to deep wells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Various research works confirmed and discussed this negative outcome [48]. On-ground contaminants are easily infiltrated and leached to the shallow wells, whereas deep wells are more protected [2]. Infiltrated contaminated water follows mixing processes through its way to deep wells.…”
Section: Discussionmentioning
confidence: 99%
“…Agrochemical applications could be the main reason for groundwater contamination [72]. Farmers extensively use agrochemicals to enhance their food production and to maximize their profits [2]. The best water potability was recorded under rough grazing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations